War of Intervention in Angola, Volume 5: Angolan and Cuban Air Forces, 1987–1992: (Adrien Fontanellaz, Tom Cooper and José Augusto Matos) - Du Toit, Louis Michael (Scientia Militaria - South African Journal of Military Studies, 2026)
War of Intervention in Angola, Volume 5: Angolan and Cuban Air Forces, 1987–1992 by Adrien Fontanellaz, Tom Cooper and José Augusto Matos, Warwick: Helion, 2023, 76 pages, ISBN 978-1-9150-7055-5.